Dual Roles of HbA1c Variability and Body Composition for Cardiovascular Risk: A Cohort Study of 8224 Adults With Type 2 Diabetes Mellitus - Sunyoung Kim; Jiyoung Hwang; Dong Keon Yon; Hyunji Sang; Selin Woo; Ho Geol Woo; Hyunjung Lim; Jungha Park; Fei‐Yuan Hsiao; Liang‐Kung Chen; Sang Youl Rhee (Journal of Cachexia, Sarcopenia and Muscle)
ABSTRACT Background Glycaemic variability and body composition are emerging predictors of cardiovascular disease (CVD) in patients with Type 2 diabetes mellitus (T2DM); however, their combined impact remains unclear. We investigated the association among HbA1c variability, body composition parameters and cardiovascular outcomes in adults with T2DM. Methods This retrospective cohort study analysed electronic health records from a university hospital (2011–2020), including 8224 adults (mean age 58.3 years, 50.1% women) with T2DM and no history of CVD. HbA1c variability score (HVS) was defined as the percentage of successive measurements differing by ≥ 0.5% (5.5 mmol/mol). Body composition was assessed by bioimpedance analysis. The primary outcome was incident CVD (ischemic heart disease, heart failure, atrial fibrillation, stroke, myocardial infarction). Results During median follow‐up of 4.0 years, patients with high HVS (third tertile) showed significantly increased CVD risk compared to low HVS (first tertile) (adjusted hazard ratio [aHR] 1.70 [95% CI 1.13–2.40]; p < 0.010). HbA1c variability demonstrated superior cardiovascular risk prediction over fasting and postprandial glucose variability. Individuals with high HVS had significantly higher systolic blood pressure (122.72 ± 14.96 vs. 120.53 ± 14.52 mmHg, p = 0.017), HbA1c (7.72% ± 1.75% vs. 7.02% ± 1.09%, p < 0.001) and lower skeletal muscle mass (24.60 ± 5.73 vs. 25.85 ± 7.84 kg, p < 0.001). Higher appendicular skeletal muscle mass was protective against CVD (aHR 0.75 [95% CI 0.63–0.88]), while increased total fat percentage elevated CVD risk (aHR 1.10 [95% CI 1.03–1.20]). HVS correlated positively with changes in total fat percentage (β = 0.439, p < 0.001) and negatively with changes in relative appendicular skeletal muscle mass (β = −0.258, p < 0.001). In multivariate analysis, significant contributors to increased CVD risk included high HVS (aHR 1.65, p = 0.011), elevated average HbA1c (aHR 1.09, p = 0.016) and age over 65 years (aHR 1.61, p = 0.035). Conclusions HbA1c variability and body composition independently predicted cardiovascular outcomes in patients with T2DM. Higher HbA1c variability increased CVD risk by 70%, while higher appendicular muscle mass reduced risk by 25%, and higher total fat percentage increased risk by 10%. Incorporating these parameters into risk stratification models could enhance cardiovascular risk prediction and guide preventive strategies for diabetes management.